The reliability of a rotational power assessment of the core - Zois, J.; Sharp, A. P.; Talukdar, K.; Cronin, J. (Journal of Athletic Enhancement, 2016)
Context: Most athletic upper-body power generation involves high levels of neuromuscular activation/coordination of a rotational nature. Therefore, it is important to assess athletic ability that replicates the rotational activity of athletes. However, a paucity of research currently measures rotational power of the core.